Mandiri Pangan dan Mandiri Financial dengan Integrated Farming sebagai Solusi Pencegahan Stunting di Desa Permata Baru, Indralaya Utara, Ogan Ilir - Adelina Irmayani Lubis; Jafar Arifin; Muhammad Naufan Rizqullah; Ayu Prameswari; Swara Mega; Deni Saputra; Agil Maulidina (Jurnal SOLMA, 2026)
Background: This community service program aimed to enhance the knowledge, skills, and family food self-sufficiency. The activity was carried out by implementing integrated farming as a stunting prevention strategy for families with toddlers in Permata Baru Village, Indralaya Utara District, Ogan Ilir Regency. The program was conducted from August to December 2025. Method: The method consisted of structured training, practical demonstrations, implementation of home yard utilization, monitoring, and evaluation. A total of 17 mothers of young children participated, and four families were selected as demonstration plots and pilot houses for implementing the Integrated farming model. Results: The results indicate an increase in participants’ knowledge with 76,5%. Participants agreed on the benefits of an integrated farming system and improved practical skills in planting vegetables, raising chickens and catfish, and processing organic waste into maggot feed and compost. In addition, it was able to reduce household consumption expenses, produce independent feed, and, on a broader scale, can later be processed for sale. Participants also showed strong enthusiasm and commitment to implementing Integrated farming independently to provide nutritious food and improve the family economy. Conclusion: This activity has proven effective in supporting family food security and financial independence and has the potential to serve as a model for community empowerment, leveraging local potential to accelerate the reduction of stunting.